Hydration products in water suspension of Portland cement containing carbonates of various solubility - Medvešček, Simona (Acta chimica slovenica, 2006)
The development of hydrated phases and overall microstructure were studied in the course of the hydration of portland cement containing carbonates of various solubility. Phase composition of hydrated samples was examined by powder diffraction and thermogravimetric analysis (TG/DTG). The development of hydrated surfaces was assessed by the measurement of surface area.
Keywords: anorganska kemija; hidratacija; karbonati; Portlandski cement; termogravimetrija